Building Independent Technical Reading Skills in English as Foreign Language Students: Desarrollo de habilidades de lectura técnica independiente en estudiantes de inglés como lengua extranjera (Papeles, 2026)
Introduction: Interpreting technical texts is a professional competence taught in English for Specific Purposes (ESP) courses. This study explores non-native English speakers' ability to interpret technical texts with and without technological aids such as online dictionaries and translators. Methodology: The study involved 44 Chilean first-year university students from the Industrial Mechanics program who undertook their first English as Foreign Language (EFL) course. Over an eight-session intervention, students' skimming and scanning skills were developed through vocabulary-building and video analysis activities. Data were collected through reading pre-tests and post-tests, and semi-structured interviews. Descriptive statistics, Wilcoxon signed-rank tests, and thematic analysis were used for data interpretation. Results and discussions: Results indicated that 72.7% of participants (32 out of 44) successfully interpreted technical texts independently in the post-test without technological assistance. Despite the challenging transition from technology-supported to autonomous reading, most participants demonstrated sufficient comprehension skills to extract general and specific information from authentic machinery manuals. Conclusion: The findings suggest that focused reading strategy instruction can  effectively improve professional English reading skills.
Keywords: Reading ability; technical education; vocabularies; language instruction; terminology